Animal protein consumer’s perception on the welfare of production animals in Belém, Pará State, Brazil - Silva, Carlos Antônio dos Santos; Joset, Waléria Cristina Lopes; Lourenço Júnior , José de Brito; Barbosa, Antônio Vinicius Corrêa; Silva, Welligton Conceição da; Silva, Jamile Andréa Rodrigues da (Acta Scientiarum. Animal Sciences, 2021)
The objective was to identify the level of knowledge of animal protein consumers about the welfare of production animals, in Belém city, Pará State, Brazil. The survey was carried out in two supermarkets, using 401 structured questionnaires, with 10 closed questions, with a “Yes” or “No” answer, taking into consideration, for the formation of a socioeconomic profile, questions related to gender, age group, educational level and family income of the interviewees. Most consumers of animal protein from the municipality of Belém, Pará State, Brazil, recognize that these products are part of their daily diet, however, the interviewees have no knowledge about the topic, and are not willing to pay more for the product with a seal of quality, as well as showing no interest or concern with the way animals are reared or slaughtered. The age group of consumers influences the level of knowledge about the welfare of production animals, observing that consumers aged 40 to 50 years have more knowledge on the subject. Education was a decisive factor in determining the level of knowledge of animal protein consumers about the welfare of production animals, as consumers from high school had more knowledge about the subject.